2000
DOI: 10.1001/archotol.126.6.759
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Tissue-Engineered Human Nasoseptal Cartilage in Simulated Microgravity

Abstract: Once combined with polyglycolic acid scaffolds in the bioreactor cascades that allow efficient seeding and quiescent tissue growth, human septal chondrocytes become a valuable source of reproducible ex vivo cartilage regeneration in the laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…Prior investigation has demonstrated that human nasal septal chondrocytes seeded into biodegradable scaffolds demonstrate poor construct structural integrity and promote fibrous rather than cartilaginous ECM deposition. 28,29,30 This is consistent with loss of the chondrogenic phenotype. It has been further noted that tissue…”
Section: Three-dimensional Culture Systemssupporting
confidence: 75%
“…Prior investigation has demonstrated that human nasal septal chondrocytes seeded into biodegradable scaffolds demonstrate poor construct structural integrity and promote fibrous rather than cartilaginous ECM deposition. 28,29,30 This is consistent with loss of the chondrogenic phenotype. It has been further noted that tissue…”
Section: Three-dimensional Culture Systemssupporting
confidence: 75%
“…These scaffolds, usually consisting of poly‐l‐lactic acid, polyglycolic acid, or a copolymer, comprise a woven mesh that traps free chondrocytes. 20 Prior studies involving human nasal septal chondrocytes seeded into biodegradable scaffolds demonstrated a lack of structural integrity 1 and lacked adequate characterization of the differentiated chondrocyte phenotype. 3 In addition, a recent study indicates that polyglycolic acid scaffolds tend to hold human septal chondrocytes in a two‐dimensional rather than in a three‐dimensional array.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in tissue engineering of nasal septal cartilage has focused on the use of biodegradable scaffolds for neocartilage formation. 1–3 However, these studies describe neocartilage lacking structural integrity. In addition, neocartilage engineered from human septal cells passaged in monolayer loses chondrocyte characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…After decalcification with 5% EDTA-2Na solution for 5 days at 4°C, some specimens were soaked in 20% sucrose-containing PBS prior to embedding into OCT compound for cryostat sectioning (Micron, Heidelberg, Germany), and others were dehydrated chondrocyte differentiation and endochondral bone formation (8,9,23,24,27). More recently, novel strategies of tissue engineering have utilized microgravity (12,19) and hypergravity (17) as aids for optimizing cartilaginous tissue growth. Nowadays, mankind's enterprises in space are no longer science fiction, but significant biological, psychological and environmental problems are yet to be addressed (25).…”
Section: Methodsmentioning
confidence: 99%